Kontekstualisasi Filologi dalam Teks-teks Islam Nusantara - Khabibi Muhammad Luthfi (IBDA': Jurnal Kebudayaan Islam, 2016)
This paper aims to explore the concepts, methods and significance of philology Islam Nusantara and contextualization in manuscripts from Indonesia. It departs from the problems that the Islamic manuscripts archipelago that has not been widely studied, whereas in it save the value, thought and culture of the past scholars Nusantara which would clarify the concept of Islam Nusantara itself. With the approach of descriptive data-based literature and discourse analysis found that the concepts, methods and significance of philology Islam Nusantara almost the same as philology in general and the only difference being the object of study, in addition to the contextualization as an approach to the study of Islam in Indonesia, particularly related to Islamic manuscripts archipelago could be advised to use The new philology without leaving classical philology.